2014
DOI: 10.3389/fnsys.2014.00159
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation for memory enhancement: from clinical research to animal models

Abstract: There is a growing demand for new brain-enhancing technologies to improve mental performance, both for patients with cognitive disorders and for healthy individuals. Transcranial direct current stimulation (tDCS) is a non-invasive, painless, and easy to use neuromodulatory technique that can improve performance on a variety of cognitive tasks in humans despite its exact mode of action remains unclear. We have conducted a mini-review of the literature to first briefly summarize the growing amount of data from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 66 publications
1
59
0
Order By: Relevance
“…However, the results of that particular experiment have not been peer-reviewed yet, and questions may be raised about the generalizability of results from cadaver studies to living human beings. Recently, several animal studies have been performed to gain more insight into how tES modulates neural function (Bennabi et al, 2014). Translational studies may help to shed light on the exact working mechanisms of tES in the future.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of that particular experiment have not been peer-reviewed yet, and questions may be raised about the generalizability of results from cadaver studies to living human beings. Recently, several animal studies have been performed to gain more insight into how tES modulates neural function (Bennabi et al, 2014). Translational studies may help to shed light on the exact working mechanisms of tES in the future.…”
Section: Introductionmentioning
confidence: 99%
“…TDCS effects on underlying cortical excitability (Nitsche and Paulus, 2000; Nitsche et al, 2005) have led to measurable changes in behavior following stimulation over lateral prefrontal (Gladwin et al, 2012; Leite et al, 2013; Minati et al, 2012; Nelson et al, 2014; Pope et al, 2015) or posterior parietal cortex (Berryhill & Jones, 2012; Manenti, Brambilla, Petesi, Ferrari, & Cotelli, 2013; Moos, Vossel, Weidner, Sparing, & Fink, 2012; Pergolizzi & Chua, 2016, 2015; Pisoni et al, 2015). Of particular interest here is that tDCS has been useful for investigating the causal role of various neocortical regions in memory processes (Bennabi et al, 2014; Brasil-Neto, 2012; Manenti et al, 2012). For example, administration of bilateral tDCS over lateral parietal cortex during retrieval resulted in increased false recognition using a paradigm known to elicit high rates of false recognition (Pergolizzi & Chua, 2015), and decreased false recognition on an item and source memory paradigm (Pergolizzi and Chua, 2016), consistent with task dependent changes in decision bias.…”
Section: Introductionmentioning
confidence: 99%
“…Berlim et al, 2013; Brunoni et al, 2012; Kuo et al, 2014), memory disorders ( e.g. Bennabi et al, 2014) and addiction (Feil and Zangen, 2010). For example, studies found that repeated tDCS over the prefrontal cortex decreased craving for, and the consumption of, cigarettes (Boggio et al, 2009; Fecteau et al, 2014; Fregni et al, 2008) and alcohol (Boggio et al, 2008; Klauss et al, 2014) in chronic users.…”
Section: Introductionmentioning
confidence: 99%